HEALTH EDUCATION TERHADAP PENGETAHUANIBU TENTANG PERAWATAN BAYI BERAT LAHIR RENDAH DI RUANG TERATAI RSUD DR.HARJONO PONOROGO - Catur Wulandari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Low birth weight babies (BBLR) is still a problem worldwide because it is acause of morbidity and mortality in the newborn, especially during the perinatal period.LBW care is good and true will improve the quality of life LBW so avoid the risk ofgrowth and developmental disorders and death. The purpose of the study to determine theeffect of health education on mother's knowledge about the care of Low Birth WeightBaby in Teratai Room Dr.Harjono Ponorogo Hospital.Pre-experimental research design with One Group Pretest-Posttest approach.The study was conducted 1-31 December 2018. The population is all mothers with LowBirth Weight Infants in Teratai Room Dr. Harjono Ponorogo a total of 37 people and asample of 31 people, with accidental sampling The independent variable is healtheducation and the dependent variable is knowledge. Instruments with quesionare.Statistical test using wilcoxon signed rank test with α = 0.05.The result of knowledge before health education is mostly 16 respondents(51,6%) enough and after health education mostly 18 respondents (58,1%) goodknowledge, p value 0,000 ≤ α 0,05 there is influence of health education to motherknowledge about care of Low Birth Weight Infant in Teratai room of RSUD Dr.HarjonoPonorogo.Nurses can improve the quality and quantity of health education activities inLotus room so that the knowledge of mother be good and can do care of Low BirthWeight at home.